Narodna identiteta pri Beneških Slovencih in Furlanih danes - Zuljan Kumar, Danila (Jezik in slovstvo, 2016)
In the Udine province of Friuli-Venezia Giulia, Slovenian and Friulian are increasingly seen and heard in public life, i.e., outside the private sphere and beyond Slovenian and Friulian institutional frameworks. The present article deals with changes in the perception of their mother tongue among representatives of both communities in relation to the prevailing Italian language, the use of which was associated with a more prestigious position in society in the past. It also investigates changes in the attitude of the majority population towards the two minority languages. The changes of discourse practices are occurring in parallel with changes in the communities' identity practices. This process is not an exception in Europe and can be placed within the wider (European) process of regionalisation
Keywords: Beneški Slovenci; Slovene; slovenščina; furlanščina; nacionalna identiteta; Furlanija Julijska krajina; Slovenes; Slovenci; Furlani